AL-MAW’IZAH AL-HASANAH (Telaah atas Metode Dakwah Dalam al-Qur’an Dan al-Sunnah) - Bakar, Abu (IAIN Ponorogo, 2015)
Abstract: During its development, al-Qur’an has become a central point in the life of every Muslim. As guidance for all mankind (hudan li al-na>s, as the rule of law, and the rule of life, al-Qur’an has become a reference in any Muslim behaviors. For a Muslim, al-Qur'an is not only a text to be read and understood, but the text also offers solutions to solve problems. One of the important themes in al-Qur'an is methods of missionary endeavor by al-maw'izah al-hasanah. The method that conducted by the Prophet in preaching rhetoric is al-maw'izah al-hasanah. Through this paper, the writer wanted to explain methods of al-maw'izah al-hasanah that contained in the Qur'an, and whatever its contained in the al-maw'izah al-hasanah hence al-Quran makes one of missionary endeavor methods. The concept of al-maw'izah al-hasanah in al-Qur’an repeated 20 times but its concept are not calculated at al-Sunnah. Al-maw'izah al-hasanah means advice kindness, goodness educating, guiding goodness. And the Prophet developed three methods of preaching throughout his life with wisdom methods, method of al-maw'izah al-hasanah and method muja>dalah. Furthermore, the forms of al-maw'izah al-hasanah are: 1) clear and gentle statements 2) polite and reachable 3 memorable stories 4) Praise and reflection 5) motivated and treated. Through those forms, endeavors become acceptable and not boring. Keywords: Muja>dalah, Qawl Layyin, Sasaran Dakwah dan Metode Dakwah